Refining restraint techniques for research pigs through habituation - O'Malley, Carly I.; Hubley, Raina; Tambadou, Halimatou; Turner, Patricia V. (Frontiers in Veterinary Science, 2022)
Pigs are common research models and are strong animals that can be difficult to restrain. Improper restraint can put pigs and research personnel at risk for injury and induce stress, which can affect research outcomes. This study aimed to refine restraint techniques for research pigs using habituation and operant conditioning. Forty-four (22 males, 22 females; 4 m.o., ~ 8.1 kg) Göttingen minipigs were randomly assigned to a control (C: no interventions) or a treatment group (T). Pigs in the T group received 3 min training sessions 3 days/week for the first 14d after arrival. Training sessions included human socialization and habituation to a hammock sling for blood collection. Blood collection occurred on day 13 for all pigs by novel technicians. Pigs were placed in the sling, blood was collected from the radial vein, and serum cortisol levels were determined (ug/dL). Pig behavior was recorded and scored for duration of time spent struggling (s) and vocalizing (s). Novel human approach tests occurred on day 12, before blood collection, and day 14, after blood collection. Pigs were scored on latency to touch the human (s) and duration of time spent in contact with the human (s). Pig weight was taken upon arrival and on day 15. Separate linear models were fitted for response variables struggle duration in sling, serum cortisol, latency to touch human, time spent in contact with human, and body weight. Fixed effects were treatment and sex. Prior to blood collection, there was no difference in response to a novel human (P>0.05) but after blood collection, T pigs were quicker to approach (estimate: -5.352, SE: 1.72, P=0.003) and spent more time in contact with the novel human (estimate: 3.091, SE: 1.448, P=0.039). T pigs also had lower cortisol levels during blood collection (estimate: -2.36, SE: 0.657, P=0.001). There was no difference in behavior while in the sling (P>0.05). The results of the study suggest that even small investments in habituation and training pigs to study procedures is beneficial in reducing stress and improving human-animal relationships, but more time would be beneficial to promote calmer behavior in the sling.